DESAIN BAHAN AJAR BERBASIS KEMAMPUAN KONEKSI MATEMATIS DENGAN METODE DISCOVERY LEARNING - Firda Nur'fauziyyah; Laelasari Laelasari; Anggita Maharani (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
This research is motivated by the low ability of mathematical connections of students with the discovery of learning barriers (obstacles to learning) specifically obstacle epistemological learning on statistical materials. One way that can be done to overcome the barriers to learning is by making the design of teaching materials. The purpose of this study is to describe learning barriers that occur between them and connect it with the design of mathematical-based learning with discovery learning method on statistical materials. This research is qualitative. Technique of writing data is done through test and interview. Subjects in this study were 34 students of class XI IPS 1 SMA Negeri 3 Kuningan. This research is didactic design or Didactical Design Research (DDR) which consists of three stages, namely: daily analysis, metapedadtive analysis, and retrospective analysis. This research is only up to the stage of expert validation. The results of this study indicate limited learning barriers. Material related to statistics. Validation of teaching materials is done by three experts, namely two lecturers of Unpad FM Mathematics and a mathematics teacher of SMA Negeri 3 Kuningan. Based on the validation results, the amount of 90.67% is obtained. Therefore, the teaching materials can be stopped very valid and can be used in the learning process.